Overactivation of the androgen receptor exacerbates gravid uterine ferroptosis via interaction with and suppression of the NRF2 defense signaling pathway. Issue 6 (26th January 2022) - Hu, Min; Zhang, Yuehui; Lu, Lingjing; Zhou, Yu; Wu, Denghui; Brännström, Mats; Shao, Linus R.; Billig, Håkan
Abstract : The mechanisms through which the androgen‐dependent activation of the androgen receptor (AR) regulates gravid uterine ferroptosis remain unknown. We show that while co‐exposure of pregnant rats to the androgen 5α‐dihydrotestosterone (DHT) and insulin (INS) triggered uterine ferroptotic signaling cascades, additional treatment with the anti‐androgen flutamide increased expression of the key ferroptosis‐inhibitory proteins SLC7A11, GSH, and GPX4; reduced iron content; normalized levels of ferroptosis‐associated Tfrc, Fpn1, and Ho1 mRNAs; reduced levels of proteins modified by 4‐HNE (a marker of ferroptosis); and restored protein levels of NRF2, a key transcription factor regulating antioxidant defense signaling, in the gravid uterus. Furthermore, exposure to DHT alone increased uterine ferroptosis, and NRF2 abundance was negatively correlated with AR status. Co‐immunoprecipitation and Western blot assays revealed that the AR physically interacted with endogenous NRF2, and this interaction was increased by DHT exposure in vivo . Our results suggest that AR overactivation and NRF2 suppression cooperate in the regulation of NRF2‐targets in uterine ferroptosis. Abstract : This study shows that in polycystic ovary syndrome (PCOS), uterine ferroptotic signaling cascades are triggered, as evidenced by suppressed SLC7A11/GSH/GPX4 signaling, impaired iron metabolism, and increased lipid peroxidation, through an androgen receptor (AR)–dependent mechanism. Long‐term exposure to 5α‐dihydrotestosterone (DHT) increases the interaction of the uterine AR with the transcription factor NRF2, leading to suppressed NRF2 antioxidative capacity and eventually promoting uterine ferroptosis.